FunRich enables enrichment analysis of OMICs datasets. Issue 11 (28th May 2021) - Fonseka, Pamali; Pathan, Mohashin; Chitti, Sai V.; Kang, Taeyoung; Mathivanan, Suresh
Graphical abstract: Highlights: FunRich is an easy and free to use tool that enables biologists to perform enrichment analysis. FunRich provides publication quality images with full option to edit font and colors. FunRich allows the users to update background databases in real time. FunRich is compatible with custom databases. Users can produce Venn diagram, Heatmap, network and enrichment analysis without the support of bioinformaticians. Abstract: High‐throughput methods to profile the genome, transcriptome, proteome and metabolome of various systems has become a routine in multiple research laboratories around the world. Hence, to analyse and interpret these heterogenous datasets user‐friendly bioinformatics tools are needed. Here, we discuss FunRich tool that enables biologists to perform functional enrichment analysis on the generated datasets. Users can perform enrichment analysis with a variety of background databases and have complete control in updating or modifying the content in most of the databases. Specifically, users can download and update the background database from UniProt at any time thereby allowing a robust background database that can support annotations from >18 taxonomies. Users can create customizable Venn diagrams, pie charts, bar graphs and heatmaps of publication quality for their datasets using FunRich (http://www.funrich.org ). Overall, FunRich tool is user-friendly and enables users to perform various analysis on their datasets with minimal or no aid from bioinformaticians.